A pair of two－component regulatory genes ecrA1／A2 in S. coelicolor - 李永泉 岑沛霖 陈时飞 吴凡 郑静 (Journal of Zhejiang University. Science, 2004)
Two-component genes are kinds of genetic elements involved in regulation of antibiotic production in Streptomyces coelicolor. DNA microarray analysis revealed that ecrA1/A2, which mapped at distant sites from red locus and encode respectively the kinase and regulator, expressed coordinately with genes of Red specific biosynthetic pathway, ecrA1 and ecrA2 gene-disruptive mutants were constructed using homogenotisation by reciprocal double crossover. Fermentation data showed that the undecylprodigiosin (Red) level of production was lower than that of wild-type strain. However, the change of the actinorhodin (Act) production level was not significant compared with wild type. Thus, these experiment results confirmed that the two-component system ecrA 1/A2 was positive regulatory element for red gene cluster.